Multivariate genetic analysis and diversity assessment in lotus (Nelumbo nucifera) accessions - KUMAR, G ASHOK; SUNDAR, S T BINI; JASMINE, A JAYA; VASANTH, S (The Indian Journal of Agricultural Sciences, 2024)
The present study was carried out during 2019 to 2022 at the Floriculture Research Station (Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu), Thovalai, Kanyakumari, Tamil Nadu to access the genetic variability in lotus accessions (Nelumbo nucifera) collected from 6 diverse locations. The research presents significant insights into the growth and flowering characteristics of these extraordinary aquatic plants and their adaptability to various environmental conditions. The analysis of mean performance showcases noteworthy variations in plant height, leaf dimensions, flowering time and the number of leaves, and flowers/plant across different collection sites, highlighting the profound influence of local environmental conditions on lotus growth. Lotus traits with significant genetic diversity and heritability, presenting opportunities for targeted selective breeding were identified. Principal component analysis uncovers key trait influencers, while cluster analysis categorizes accessions based on similarities, streamlining research and cultivation. Correlation and path analysis unveil relationships among lotus traits, enhancing our understanding of growth factors. D2 cluster composition reveals distinct groupings; Cluster I includes KNn1 and KNn5, Cluster II features KNn2, Cluster III comprises KNn6, Cluster IV contains KNn3, and Cluster V houses KNn4. Genetic divergence analysis identifies the number of flowers/plant as the primary driver of genetic diversity, emphasizing its importance for breeding. It underscores the need to consider both genetic and environmental factors in lotus cultivation and highlights the importance of targeted breeding efforts to unlock the full potential of lotus.